POSEY’S VOLUNTARY AND INTENTIONAL BEHAVIORS IN MITCH ALBOM’S FOR ONE MORE DAY - Ramadhani, Riska Dewi; Kirana, Kheista Sasi; Nurdin, Dewi Syifanaya Firdausy; Wijayanto, Bagus Pratama; Pasopati, Rommel Utungga (Universitas Negeri Surabaya, 2025)
This study explores the altruistic qualities of Posey, the main character in Mitch Albom’s novel For One More Day, focusing on her voluntary and intentional behaviors as expressions of altruism. Altruism is defined as selfless concern for the welfare of others, often manifested without expectation of reward. Using qualitative methods and character analysis, this study examines Posey’s acts of sacrifice, emotional support, and moral guidance, specifically in her relationship with her son, Charley Benetto. Her behaviors—from defending her son against unfair judgment to creating lasting emotional bonds—are voluntary and intentional, reflecting a deep commitment to the welfare of others. In conclusion, this study confirms that altruism in the literature can be explained by consistent and intentional actions that prioritize the needs of others over personal gain.